The legal remedy against the execution of an auction that does not yet have a winner is an objection - Gitayana Amalia; Maddenleo T Siagian (Priviet Social Sciences Journal, 2025)
The execution of a mortgage auction often serves as a legal mechanism for generating disputes between creditors and debtors. Conflicts typically arise when a debtor files a lawsuit challenging an auction process that has not yet been completed, particularly when no winning bidder has been determined yet. This study examines the Supreme Court of the Republic of Indonesia’s Decision No. 2644 K/Pdt/2023 clarifies that the proper legal remedy against an unfinished auction process is not a lawsuit but rather an execution objection (perlawanan eksekusi). Employing a normative juridical method, the research adopts both statutory and case study approaches to analyze the Court’s reasoning and its implications for legal practice. The findings reveal that the Supreme Court establishes execution objection as the sole appropriate legal action at this stage to uphold legal certainty and the effectiveness of the mortgage enforcement process. Nevertheless, protecting the debtor’s rights remains a critical consideration, particularly through mechanisms that ensure adequate notification and access to legal remedies. This decision underscores the court’s effort to balance procedural efficiency with fairness, preventing unnecessary disruption of the execution process while safeguarding the debtor’s opportunity to challenge procedural irregularities. In conclusion, the ruling provides an important precedent for distinguishing between permissible and impermissible legal remedies during the auction execution phase, reinforcing the principle that disputes concerning incomplete auctions must be resolved through execution objections rather than civil litigation.